2013
DOI: 10.1096/fj.12-221127
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial resistance mechanism: what proteomics can elucidate

Abstract: Antibiotics are important therapeutic agents commonly used for the control of bacterial infectious diseases; however, resistance to antibiotics has become a global public health problem. Therefore, effective therapy in the treatment of resistant bacteria is necessary and, to achieve this, a detailed understanding of mechanisms that underlie drug resistance must be sought. To fill the multiple gaps that remain in understanding bacterial resistance, proteomic tools have been used to study bacterial physiology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 103 publications
3
46
1
1
Order By: Relevance
“…To ensure the correct assignment of isolates in the overlapping zone, either additional investigations on the presence of potential resistance mechanisms or a relatively wide intermediate zone is required (12). Increasing knowledge of the different molecular resistance mechanisms present in clinical isolates will allow establishment of resistotype-associated RCOFF values, facilitating the correlation of the in vitro AST data with the clinical outcome, a prerequisite for the setting and validation of CBPs (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the correct assignment of isolates in the overlapping zone, either additional investigations on the presence of potential resistance mechanisms or a relatively wide intermediate zone is required (12). Increasing knowledge of the different molecular resistance mechanisms present in clinical isolates will allow establishment of resistotype-associated RCOFF values, facilitating the correlation of the in vitro AST data with the clinical outcome, a prerequisite for the setting and validation of CBPs (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Ejemplo de ello son las mutaciones DNA topoisomerasas gyrA, gyrB y parC, responsables de la resistencia a fluoroquinolonas en Coxiella burnetii (Lima et al, 2013).…”
Section: Mutaciones Del Genunclassified
“…In a shotgun-based proteomic study an altered outer membrane protein profile was found in clarithromycin resistant Helicobacter pylori (Smiley et al, 2013). Further proteomic based studies describing the importance of OMPs is extensively described elsewhere (Lima et al, 2013).…”
Section: Proteomics Of Membrane Proteins Involved In Virulencementioning
confidence: 99%